2003
DOI: 10.1159/000075666
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-<i>fos</i> in the Brain after Activation of L-Type Calcium Channels

Abstract: In rodents, administration of the L-type calcium channel activators, ±Bay K 8644 and FPL 64176, causes an unusual neurobehavioral syndrome that includes dystonia and self-injurious biting. To determine the regional influence of these drugs in the brain, the induction of c-fos was mapped after administration of these drugs to mice. In situ hybridization with an antisense riboprobe directed to c-fos mRNA revealed widespread induction, with the highest levels in the striatum, cortex, hippocampus, locus coeruleus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In the current study participation of central emetic neurons in FPL64176-induced vomiting is further indicated by upregulated c-Fos expression in brainstem emetic nuclei NTS, a key site for integration of diverse emetic signals (Ray et al, 2009a and 2009c), and DMNX, which receives axonal projections from NTS (Travagli and Anselmi, 2016). Thus, the blood-brain barrier permeable agent FPL64176 (Jinnah et al, 1999; 2000 and 2003) could excite emetic neurons directly in the NTS and DMNX. The absence of expected increase in Fos-immunoreactivity in the AP may be explained by findings that systemic administration of some emetics may not involve the AP (Miller and Leslie, 1994; Ray et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study participation of central emetic neurons in FPL64176-induced vomiting is further indicated by upregulated c-Fos expression in brainstem emetic nuclei NTS, a key site for integration of diverse emetic signals (Ray et al, 2009a and 2009c), and DMNX, which receives axonal projections from NTS (Travagli and Anselmi, 2016). Thus, the blood-brain barrier permeable agent FPL64176 (Jinnah et al, 1999; 2000 and 2003) could excite emetic neurons directly in the NTS and DMNX. The absence of expected increase in Fos-immunoreactivity in the AP may be explained by findings that systemic administration of some emetics may not involve the AP (Miller and Leslie, 1994; Ray et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…The infl uence of 8 BayK 8644 on regional brain activity was recently delineated by mapping the induction of the immediate-early gene c-fos [Jinnah et al, 2004]. Despite the nearly ubiquitous expression of L-type calcium channels in the brain, these functional mapping studies revealed a heterogeneous effect on regional brain activity, with the most prominent changes in the striatum.…”
Section: Introductionmentioning
confidence: 99%
“…The present result proposes that c-fos expression in the MGv is related to the corticothalamic inputs mediated by AMPA, NMDA, and mGluR receptors. c-fos expression has been proposed to link with calcium influx, which then triggers a cascade of Ca 2ϩ -sensitive gene expression (33)(34)(35). Extracellular Ca 2ϩ influx can occur through various channels, such as NMDA receptors and L-type voltage-operated Ca 2ϩ channels (36,37).…”
Section: Discussion C-fos Expression In the Auditory Pathwaymentioning
confidence: 99%